Downregulation of mPGES-1 Expression via EGR1 Plays an Important Role in Inhibition of Caffeine on PGE2 Synthesis of HBx(+) Hepatocytes - Yan Ma; Xiaoqian Wang; Nanhong Tang (Mediators of Inflammation)
We investigated the mechanism of caffeine in influencing HBx(+) hepatocytes to synthesize PGE2. The inhibitory effect of caffeine on hepatocyte proliferation increased with increasing caffeine concentrations (200–800 μM) and treatment times (1–7 days), which was first observed at the second test time point (caffeine treatment for 4 days). The inhibition of caffeine on the growth of HL7702-HBx and HepG2-HBx cells was most obvious at 800 μM caffeine and at caffeine treatment for 7 days. The PGE2 secretion and the expression of mPGES-1 and EGR1 were downregulated, whereas PPARγ expression was upregulated. The mPGES-1 promoter activity of HBx(+) hepatocytes decreased more significantly than that of HBx(−) hepatocytes. Moreover, the expression of EGR1 and PPARγ changed more significantly in HBx(+) hepatocytes cultured for 12 to 24 hours in the presence of 5 mM caffeine. This limited success may be attributed to caffeine releasing the binding of HBx and PPARγ and furthermore affecting the mPGES-1 expression by EGR1 in HBx(+) hepatocytes. The results indicate that caffeine could effectively reduce PGE2 synthesis in HBx(+) hepatocytes by specifically blocking the PPARγ-EGR1-mPGES-1 pathway, thereby providing a new evidence of molecular biology for the hypothesis that drinking coffee is beneficial to HBV-infected patients.